Controls and requirements for Applying cybersecurity to protect data at Princess Nourah University | ضوابط ومتطلبات تطبيق الأمن السيبراني لحماية البيانات في جامعة الأميرة نورة - Al Hazani | الهزاني, Nora Bent Nacer Ben Abd Allah | نورة بنت ناصر بن عبد الله (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
The current study aimed to identify the cybersecurity controls for data protection, and to reveal the requirements for applying cybersecurity, As well as identifying obstacles to applying cybersecurity controls and requirements at Princess Noura University. To achieve the objectives of this study, the descriptive analytical approach was used through a questionnaire collected from a random sample of )352( faculty members and the like at Princess Noura University. The study reached a set of results, the most important of which is the agreement of the sample on the achievement of the cybersecurity controls dimension for data protection at Princess University with a high degree of )77.72%(, where the axis of enhancing cybersecurity ranked first with a rate of )80.6%(. About achieving the dimension of cybersecurity application requirements at Princess Noura University, which represents a percentage of )76.26%(, where the technical requirements axis came first with a percentage of )80.5%(, followed by administrative requirements with a percentage of )76.48%(, then physical requirements with a percentage of )73.68%(, then finally human requirements With a percentage of )71.94%(, and as indicated by the agreement of the opinions of the majority of the sample on the impacts of obstacles to the application of negative cybersecurity controls and requirements by )67.58%(, where it came in the first place )lack of training courses held at the university for its employees in the field of cybersecurity(, which represents )73.4%,( followed by )low level of sufficient experience among users( which represents )70.96%(, then in third place )weak cooperation between technical and academic staff in the cybersecurity program to achieve cybersecurity at the university( which represents )70.74%(. The study concluded with a set of recommendations, including the need to prepare training programs aimed at training faculty members to apply cybersecurity requirements, how to protect data from the challenges and risks of cybercrime, and the need for the university’s cybersecurity department to develop a guide for information security governance standards, and to compel Faculty members apply standards to ensure the safety and accuracy of the educational process and data protection, as well as the necessity of qualifying qualified human cadres in the field of cybersecurity and strengthening professional relations and community service in the field of applying cybersecurity.| استهدفت الدراسة الحالية التعرف على ضوابط الأمن السيبراني لحماية البيانات، والكشف عن متطلبات تطبيق الأمن السيبراني، وكذلك التعرف على معوقات تطبيقضوابط ومتطلبات الأمن السيبراني في جامعة الأميرة نورة. ولتحقيق أهداف هذه الدراسة استخدمت المنهج التحليلي الوصفي من خلال استبانة جمعت من عينة عشوائية قوامها 352من أعضاء هيئة التدريس ومن في حكمهم بجامعة الأميرة نورة. وتوصلت الدراسة إلى مجموعة من النتائج، من أهمها: اتفاق آراء العينة حول تحقق بُعد ضوابط الأمن السيبراني لحماية البيانات في الجامعة بدرجة مرتفعة، وذلك بنسبة %77.72 إذ جاء محور تعزيز الأمن السيبراني في المرتبة الأولى بنسبة %80.6كما كشفت عن اتفاق آراء العينة حول تحقق بُعد متطلبات تطبيق الأمن السيبراني في الجامعة بما يمثل نسبة % ً 76.26فقد جاء محور المتطلبات التقنية أولًا بنسبة %80.5 ويليه المتطلبات الإدارية بنسبة %76.48ثم المتطلبات المادية بنسبة %73.68ثم أخيرا المتطلبات البشرية بنسبة %71.94كما أوضحت اتفاق آراء غالبية العينة على تأثيرات معوقات تطبيق ضوابط ومتطلبات الأمن السيبراني السلبية بنسبة %67.58 فقد جاء في المرتبة الأولى «قلة الدورات التدريبية المنعقدة في الجامعة لموظفيها في مجال الأمن السيبراني» بما يمثل %73.4ويليه «تدني مستوى الخبرة الكافية لدى المستخدمين» بما يمثل %70.96ثم في المرتبة الثالثة «ضعف التعاون بين الموظفين التقنيين والأكاديميين في برنامج الأمن السيبراني لتحقيق الأمن السيبراني في الجامعة» بما يمثل %70.74وخلصت الدراسة إلى مجموعة من التوصيات، منها: ضرورة إعداد برامج تدريبية تهدف إلى تدريب أعضاء هيئة التدريس على تطبيق متطلبات الأمن السيبراني، وكيفية حماية البيانات من تحديات ومخاطر الجرائم السيبرانية، وضرورة أن تعمل إدارة الأمن السيبراني في الجامعة على وضع دليل إرشادي لمعايير حوكمة أمن المعلومات، وإلزام أعضاء هيئة التدريس بتطبيق المعايير لضمان سلامة ودقة سير العملية التعليمية وحماية البيانات، وكذلك ضرورة تأهيل الكوادر البشرية المؤهلة في تخصص الأمن السيبراني، وتعزيز العلاقات المهنية، وخدمة المجتمع في مجال تطبيق الأمن السيبراني.